Plant Growth Promoting Rhizobacteria in Amelioration of Salinity Stress: A Systems Biology Perspective - Ilangumaran, Gayathri; Smith, Donald L. (Frontiers in Plant Science, 2017)
Salinity affects plant growth and development and is a major abiotic stress that limits crop productivity. It is well understood that environmental adaptations and genetic traits regulate salinity tolerance mechanisms but imparting the knowledge gained towards crop improvement remain arduous. Harnessing the potential of beneficial microorganisms present in the rhizosphere is an alternative strategy for improving plant stress tolerance. The review intends to elucidate the understanding of salinity tolerance mechanisms attributed by plant growth promoting rhizobacteria (PGPR). Recent advances in molecular studies have yielded insights into the signaling networks of plant-bacteria interactions that contribute to salt tolerance. The beneficial effects of PGPR involve boosting key physiological processes, including water and nutrient uptake, photosynthesis and source-sink relationships that promote growth and development. The regulation of osmotic balance and ion homeostasis are conducted through modulation of phytohormone status, gene expression, protein function and metabolite synthesis in plants. As a result, improved antioxidant activity, osmolyte accumulation, proton transport machinery, salt compartmentalization and nutrient status reduce osmotic stress and ion toxicity. Furthermore, in addition to auxin and 1-aminocyclopropane-1-carboxylic acid deaminase biosynthesis, other extracellular secretions of the rhizobacteria function as signaling molecules and elicit stress responsive pathways. Application of PGPR inoculants is a promising measure to combat salinity in agricultural fields, thereby increasing global food production.